PERBAIKAN MANAJEMEN USAHA DAN PENGELOLAAN KEUANGAN USAHA PADA UMKM KERIPIK PISANG DI DESA KAMURANG KECAMATAN CIKANDE KABUPATEN SERANG - Encep Saefullah; Nani Rohaeni; Tabroni Tabroni (Yayasan Education and Social Center, 2022)
Partners in this Community Partnership Program (PKM) are the Kamurang Village Government and the manager of banana chip MSMEs in Kamurang Village, Cikande District, Serang Regency. The objectives of this Program are (1) To improve the knowledge and skills of partners in managing business management and business finances properly and correctly as well as understanding business strategies in facing conditions in the new normal era, (2) To improve and develop digital marketing in marketing or sales of partner products and transfer knowledge of the use of Appropriate Technology (TTG) in the form of making banana slicing machines, and (3) Assisting in the process of applying for a Household Industry Food Production Certificate (SPP-IRT). Using the chronological method, the implementation of this activity resulted in an increase in partner knowledge and skills about managing Business Management, Business Finance, Digital Marketing and the application of Appropriate Technology (TTG) by 81.50%.